QUALITY OF PUBLIC SERVICE FIELD GOVERNMENT IN THE TANIWEL DISTRICT OFFICE WEST SERAM DISTRICT - Rahawarin, Muhamad Arsad (JURNAL BADATI, 2021)
This study aims to analyze: (1) the quality of public services in the field of government and (2) the influence of the factors of human resources, facilities and infrastructure as well as community behavior on the quality of public services. The results show that (1) the unsatisfactory quality of ID cards and family cards services on the tangible dimension is the completeness of computers and the availability of complete information regarding the service flow, on the reliability dimension is the discipline of officers in providing services, on the responsiveness dimension all indicators are not satisfactory, namely employees. slow in providing services which is marked by a discrepancy between the service schedule and the rules that have been set, so that the final completion of ID cards and family cards is not in accordance with the required time, on the assurance dimension of guaranteeing that the completion of ID cards and family cards is in accordance with the required time, on the empathy dimension is perseverance employees in providing services, (2) the factors that influence the quality of service for ID cards and family cards are human resources, facilities and infrastructure and community behavior.